A Pre-Trial Domestic Violence Intensive Supervision Unit: Exploring Case Seriousness and Successful Disposition - Tatum, Kimberly M. (American journal of criminal justice, 2008)
This study measures the seriousness of domestic violence cases from the population of cases (N = 96) sentenced to a pre-trial domestic violence intensive supervision unit in one county probation office in Florida from April 1, 2006, to April 30, 2007. No significant differences were found in seriousness across sex, self-reported drug use, or attorney type. Furthermore, no relationship was found between the number of special conditions imposed by the court and the seriousness index value for a case. However, non-Whites had a significantly higher mean case seriousness index than Whites. Findings suggest that using the seriousness index presented in this study, some of the cases examined were not serious enough to warrant being sentenced to the pre-trial domestic violence intensive supervision unit. Implications for future research, including the use of lethality assessments, are addressed.